Seeds cryopreservation of Vriesea reitzii Leme & A.F. Costa endemic bromeliad from Atlantic Rainforest - Montoya-Serrano,Francisco S. (2022)
ABSTRACT Vriesea reitzii is an endemic bromeliad from the Atlantic Rainforest. The objective of this research was to evaluate the cryopreservation using the method of direct immersion of its seeds, collected from capsules at 120, 135, and 150 days after anthesis (DAA). The water content was determined before cryopreservation, while the germination percentage, germination speed index (GSI), and total soluble carbohydrates were quantified after cryopreservation. The highest percentage of moisture (17.6%) was observed in 120 DAA, while the highest percentage of germination (89.6%) and GSI (17.0) were observed in 150 DAA. Optical and transmission electron microscopy analyses were performed, and no cell damage or changes at the morpho-histological and ultrastructural levels were observed after the cryopreservation process. From these results, V. reitzii seeds can be classified as orthodox seeds and the cryopreservation (+LN) is an efficient tool for an ex situ conservation of this species.